(untitled) (Indonesian Journal of Civil Engineering Study, 2025)
The Bulakan – Serenan Bridge, located in Sukoharjo Regency, Central Java, serves as a key infrastructure connecting Juwiring District in Klaten Regency with Sukoharjo District in Sukoharjo Regency. With increasing traffic volume, the bridge’s safety and capacity have become primary concerns in this study. The research aims to redesign the bridge with a Warren truss type to enhance its capacity to accommodate the growing traffic demand while ensuring safety and comfort. The bridge load planning is carried out based on SNI 1725 (2016) and SNI 2833 (2016) standards, complemented by additional bridge regulations such as RSNI T-03-2005, the Bridge Management System, and Practical Guide for Bridge Engineering Design. Structural analysis is performed using ETABS Version 14 software. Traffic data and the planned structural conditions are analyzed to assess the impact of increased traffic volume on the bridge’s structural strength.